1971
DOI: 10.1083/jcb.49.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Nuclei From Yeast

Abstract: A method for isolation of nuclei from Saccharomyces cervisiae in high yield is described. The DNA/protein ratio of the isolated nuclei is 10 times higher than that of whole cells. Examination of these nuclei in phase and electron microscopes has shown them to be round bodies having a double membrane, microtubules, and a dark crescent at one end. The optimum conditions for extraction and resolution of histones of these nuclei on acrylamide gels have been investigated. The nuclei have an active RNA polymerase (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1971
1971
1982
1982

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…Fluorescence microscopy revealed that at the higher detergent concentration the nuclei appeared more disrupted, and electron microscopy showed that the nuclear membranes were removed from most nuclei. The overall recovery of DNA from A. nidulans was less than reported for S. cerevisiae (Bhargava & Halvorson, 1971;Doi & Doi, 1974;Wintersberger et al, 1973) or for the N. crassa slime mutant (Hsiang & Cole, 1973). However, our recovery was better than that of Hsiang & Cole (1973)~ who obtained a recovery of less than 10 % from wildtype N. crassa using the disruption method of Reich & Tsuda (1961).…”
Section: Nuclei In Situmentioning
confidence: 80%
See 2 more Smart Citations
“…Fluorescence microscopy revealed that at the higher detergent concentration the nuclei appeared more disrupted, and electron microscopy showed that the nuclear membranes were removed from most nuclei. The overall recovery of DNA from A. nidulans was less than reported for S. cerevisiae (Bhargava & Halvorson, 1971;Doi & Doi, 1974;Wintersberger et al, 1973) or for the N. crassa slime mutant (Hsiang & Cole, 1973). However, our recovery was better than that of Hsiang & Cole (1973)~ who obtained a recovery of less than 10 % from wildtype N. crassa using the disruption method of Reich & Tsuda (1961).…”
Section: Nuclei In Situmentioning
confidence: 80%
“…The nuclear membrane was not complete in all nuclei and this may have been a direct result of our procedure. Membrane connexions between the nucleus and endoplasmic reticulum have been described in other fungi (Bracker, 1967) and it is also possible that breakage of such a connexion during homogenization resulted in the rupture of the nuclear membrane. Nuclei which lacked part of their envelope were, nevertheless, not disrupted.…”
Section: Nuclei In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of normality involves applying the concept of balanced growth. [1][2][3][4][5][6][7][8][9][10] As defined by Campbell,10 balanced growth is the doubling of every bio chemical component of the cells within the time of one cycle without change in the rate of growth. In considering this, it must be remembered that most synchronous cultures are batch cultures and therefore the medium changes in composition during the experiment, thus tending to make growth unbalanced.…”
Section: Methods Of Studying the Cell Cyclementioning
confidence: 99%
“…Yeast RNA polymerase I, II, and III were purified from 60 g of frozen cells. Frozen cells were lysed in an Eaton press at 9000 lb/inch2 (62 MPa) (17) 10,000 X g. Nucleic acids in the clarified extract were removed by precipitation with 0.5% protamine sulfate followed by centrifugation. The protamine sulfate supernatant was diluted with two volumes of buffer A and adsorbed onto a DEAE-Sephadex A-25 column.…”
Section: Abstracimentioning
confidence: 99%